The habits of mind and its relation to mental ability according to Sternberg theory of talented students in Dammam - Al-Khaldi, Wojud Rashid Yousef (Journal of Educational and Psychological Sciences, 2018)
The study aimed to identify the habits of the mind and its relation to mental ability according to Sternberg theory of talented students in Dammam, and was used descriptive and comparative descriptive method. The study population is composed of all gifted students in Dammam city (200) and a random sample was selected (102). The results of the study showed that the habits of the mind are available for gifted students in Dammam with an average of 4.10 (5), ie, to a great extent. At the level of the habits, their average ranged from (4.16) to creativity, imagination and innovation (3.94) to thinking, . The study also confirmed that there is a statistically significant relationship at (0.01) between the degree of creativity, imagination and innovation as one of the dimensions of the habits of the mind and the total degree of mental ability of the talented students in Dammam. (0.05) between the total degree of mental habits and the total degree of mental ability of gifted students in Dammam, and the absence of a significant correlation between the degrees of the rest of the dimensions of mental habits and the total degree of mental ability of gifted students in Dammam. In the light of the results of the study, a number of recommendations and suggestions were made to increase the mental abilities of gifted students in general.